2021
DOI: 10.1177/0272989x211020317
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Patient Decision Aids for Socially Disadvantaged Populations: Update from the International Patient Decision Aid Standards (IPDAS)

Abstract: Background The effectiveness of patient decision aids (PtDAs) and other shared decision-making (SDM) interventions for socially disadvantaged populations has not been well studied. Purpose To assess whether PtDAs and other SDM interventions improve outcomes or decrease health inequalities among socially disadvantaged populations and determine the critical features of successful interventions. Data Sources MEDLINE, CINAHL, Cochrane, PsycINFO, and Web of Science from inception to October 2019. Cochrane systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 83 publications
1
31
1
Order By: Relevance
“…Recent research suggests that psychiatric patients (with several cognitive deficits) are capable of using the PtDA and can benefit from doing so [ 60 , 61 ]. A recent systematic review reported that for socially disadvantaged patients in particular, with a lower level of digital health literacy, the use of PtDA leads to better health outcomes [ 62 ]. Future projects should examine whether the level of digital health literacy is a key factor that could influence the health outcomes of patients with GAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that psychiatric patients (with several cognitive deficits) are capable of using the PtDA and can benefit from doing so [ 60 , 61 ]. A recent systematic review reported that for socially disadvantaged patients in particular, with a lower level of digital health literacy, the use of PtDA leads to better health outcomes [ 62 ]. Future projects should examine whether the level of digital health literacy is a key factor that could influence the health outcomes of patients with GAD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of DAs for people with lower health literacy [ 57 , 58 ] showed that DAs that use health literacy design strategies lead to improved knowledge, decisional conflict, and decision-making outcomes. Furthermore, DAs that used explicit strategies to reduce cognitive burden showed greater improvements in knowledge for people with low health literacy and from disadvantaged backgrounds [ 58 ]. The review highlighted the need for more consideration of health literacy in DA development.…”
Section: Discussionmentioning
confidence: 99%
“…PEMs written at a level too high for the average adult may increase the risk of promoting health disparities as shown by Sentell et al [ 33 ]. However, a recent review by Yen et al showed that the use of patient decision aids in socially disadvantaged populations has the potential to improve patient outcomes [ 34 ]. Hence it is of concern that our results show that breathlessness PEMs are written at a level too high for the average population.…”
Section: Discussionmentioning
confidence: 99%